Effect of upgrading primary feeders from radial to loop arrangement on electrical distribution system performance - Peerapol Jirapong (2018)
© 2015 IEEE. This paper presents an analytical assessment of upgrading primary electrical feeders from a radial to a normally closed-loop arrangement in an existing distribution system. Distribution system performance, including system power loss reduction, feeder loading conditions, voltage profile improvement, and reliability enhancement in the system was evaluated and analyzed using DIgSILENT PowerFactory software. An existing 115 kV radial distribution system with two primary feeders in Chiang Mai province from the Provincial Electricity Authority (PEA) of Thailand was used as a case study. The distribution system data from a Geographic Information System (GIS) database were imported to the simulation software using the DIgSILENT-GIS-SCADA (DGS) file format. Different scenarios of transformer loading and primary feeder configuration were considered to study the performance and effectiveness of the system rearrangement. Our assessment showed that the efficient and effective system upgrading results in system power loss reduction, voltage profile improvement, and a significant reliability enhancement leading to a higher level of system performance.